Effects of Acute Laboratory Stress on Executive Functions - Starcke, Katrin; Wiesen, Carina; Trotzke, Patrick; Brand, Matthias (Frontiers in Psychology, 2016)
Recent research indicates that stress can affect executive functioning. However, previous results are mixed with respect to the direction and size of effects, especially when considering different subcomponents of executive functions. The current study systematically investigates the effects of stress on the five components of executive functions proposed by Smith and Jonides (1999): attention and inhibition; task management; planning; monitoring; and coding. Healthy participants (N = 40) were either exposed to the computerized version of the Paced Auditory Serial Addition Test as a stressor (N = 20), or to a rest condition (N = 20). Stress reactions were assessed with heart rate and subjective measures. After the experimental manipulation, all participants performed tasks that measure the different executive functions. The manipulation check indicates that stress induction was successful (i.e., the stress group showed a higher heart rate and higher subjective responses than the control group). The main results demonstrate that stressed participants show a poorer performance compared with unstressed participants in all executive subcomponents, with the exception of monitoring. Effect sizes for the tasks that reveal differences between stressed and unstressed participants are high. We conclude that the laboratory stressor used here overall reduced executive functioning.